Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = - ( 5 - 6 ) - ( 3 - 4 + 5 - 7 )
A = -5 + 6 - 3 + 4 - 5 + 7
A = ( 6 + 4 ) + ( -5 + (-5) ) + ( -3 + 7 )
A = 10 + (-10) + 4
A = 0 + 4
A = 4
P = ( 1 + 3 + 5 + ... + 47 + 49 ) - ( 2 + 4 + 6 + ... + 48 + 50 )
P = \(\frac{\left(1+49\right)\cdot\left(\left(49-1\right):2+1\right)}{2}\) - \(\frac{\left(2+50\right)\cdot\left(\left(50-2\right):2+1\right)}{2}\)
P = \(625-650\)
P = \(-25\)
\(B=1.2.3+2.3.4+3.4.5+.......+49.50.51\)
\(\Rightarrow4B=1.2.3.4+2.3.4.4+3.4.5.4+.......+49.50.51.4\)
\(=1.2.3.4+2.3.4\left(5-1\right)+3.4.5\left(6-2\right)+.........+49.50.51.\left(52-48\right)\)
\(=1.2.3.4+2.3.4.5-1.2.3.4+3.4.5.6-2.3.4.5+.........+49.50.51.52-48.49.50.51\)
\(=49.50.51.52\)
\(\Rightarrow B=\frac{49.50.51.52}{4}=1624350\)
B = 4 + 43 + 45 +.....+449
42.B = 43 + 45+......+449 + 451
16B - B = 451 - 4
15B = ( 451-4)
B = (451 - 4): 16